Polymetamorphic evolution of nepheline normative rocks in the Skattøra migmatite complex, Tromsø, North Norway - Knutsen, Marianne Leinan (Universitetet i Tromsø, 2012)
The Skattøra migmatite complex (SMC) in the north Norwegian Caledonides is a slightly nepheline normative migmatitic meta-cumulate rock sequence, which experienced anatexis under water saturated conditions. In situ- and local crystallization of melt is reflected by leucosomes and the numerous anorthositic dykes net veining the rock complex. Studies of quartz-free rocks gives challenges for implying P-T conditions by traditional geothermobarometric methods. Phase transitions during metamorphism, partial melting metasomatism in the SMC has been studied through optical petrography and bulk chemistry, and pseudosection-modelling has been the main tool for investigating phase topologies and quantifying P-T conditions during evolution of the SMC. Minimum limit for metamorphic peak conditions in the anorthositic part of the complex is suggested to be approximately 1.18 GPa in the temperature interval 800-850 ⁰C. In more complex chemical systems onset of melting occurred at lower temperatures. In the context of the tectonometamorphic evolution of the Upper Most Allochthon results for high grade metamorphism are supportive of earlier work, while for the late retrogressive stage additional suggestions are presented. The discovery of cross-cutting dolerite dykes in the SMC adds a new feature that should be addressed in future studies.